Alloy powder suitable for laser surfacing of garbage incinerator and preparation method of alloy powder

By using specific alloy powders in waste incinerators for laser surfacing, the complex corrosion environment and high-temperature wear are solved, and the long-term stable operation and safety improvement of the equipment are achieved.

CN119457573APending Publication Date: 2025-02-18SHANGHAI ZHUYU MATERIAL TECH CO
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510053150.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

There are complex corrosion environments and high-temperature erosion and wear problems in waste incinerators, resulting in rapid oxidation, corrosion and wear of the heated surface tubes, thereby increasing safety hazards and maintenance costs.

Method used

Using a specific alloy powder, including Cr, Mo, Nb, Fe, Sc, Al, Ti, Si, etc., it is prepared by vacuum smelting and atomization granulation processes to form an alloy with excellent corrosion resistance and high temperature wear resistance. Powder, used for laser surfacing of waste incinerators.

Benefits of technology

In the harsh environment of waste incinerators, the cladding layer formed significantly improves the service life and safety of the equipment, reduces faults and maintenance costs caused by corrosion and wear, and improves the operating efficiency and reliability of the waste incineration system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of alloy materials, in particular to alloy powder suitable for laser surfacing of a garbage incinerator and a preparation method of the alloy powder. The alloy powder comprises the following components in percentage by mass: less than or equal to 0.10% of C, 20.0-23.0% of Cr, 8.0-10.0% of Mo, 3.15-4.15% of Nb, less than or equal to 0.50% of Fe, less than or equal to 0.005% of Sc, less than or equal to 0.40% of Al, less than or equal to 0.40% of Ti, less than or equal to 1.0% of Si and the balance of Ni; the preparation method comprises the following steps: burdening according to the formula ratio, then feeding the raw materials into a vacuum melting chamber, and carrying out vacuum-pumping treatment; and through electromagnetic induction, metal raw materials are molten into metal liquid, and the metal liquid enters the atomizing chamber through the flow guide pipe for atomizing granulation. By elaborately designing the composition of the alloy powder, particularly introducing the rare earth element Sc, the crystal grains are refined, and the defects at the grain boundary are reduced, so that the cladding layer formed after the alloy powder serving as welding powder is subjected to laser surfacing has excellent wear resistance and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of alloy materials, and in particular to an alloy powder suitable for laser surfacing welding of a waste incinerator and a preparation method thereof. Background Art

[0002] In recent years, the proportion of plastic products and plastic packaging materials in garbage has continued to increase. Synthetic resins in garbage, such as polyvinyl chloride (PVC), artificial rubber, artificial leather, foam plastics, etc., contain more organic chlorides, while kitchen garbage contains inorganic chlorides such as sodium chloride, potassium chloride and magnesium chloride, resulting in increased concentrations of various organic and inorganic chlorines in flue gas. Under high temperatures, Cl often appears in the incineration environment in the form of gaseous HCl, Cl2 and metal chlorides KCl, NaCl, ZnCl2, PbCl2 and other deposits, resulting in several forms of corrosion: One is gas phase corrosion: in the high temperature chlorine-containing atmosphere of the incinerator, gas phase corrosion is directly caused; The second is redox corrosion: the low-melting-point ash deposited salt of metal chloride reacts with the chloride film on the metal surface to corrode the substrate; The third is electrochemical corrosion: metal chlorides and other inorganic salts in the flue gas are deposited on the metal surface together to form low-melting-point eutectics, which greatly reduce the melting point of the ash deposits, produce molten corrosive salts on the high-temperature tube wall, and form a local liquid phase at the ash-metal interface, forming an electrochemical corrosion atmosphere. The base metal undergoes anodic dissolution, and the two oxidants O2 and Cl2 in the atmosphere are reduced accordingly. The base metal is further oxidized and combined with loose oxide particles to form deposits, or with Cl - Combined to form chloride, as the corrosion progresses, a loose outer oxide film is formed on the outer surface of the molten chloride. Due to the high diffusion rate of metal ions in molten salts, this electrochemical process seriously corrodes the (heating surface) superheater and water-cooled wall of the waste incineration waste heat boiler.

[0003] Moreover, the actual operating temperature of boilers is getting higher and higher. If the boiler heating surface is not cleaned in time or the cleaning effect is not good, the heat transfer of the heating surface will be blocked, resulting in excessive surface temperature of the heating surface. High-temperature corrosion will coexist with S corrosion (i.e., corrosion of Na3Fe(SO4)3 and K3Fe(SO4)3) and the aforementioned Cl corrosion. S corrosion is mainly manifested in the form of thermal corrosion of alkali metals. The high temperature environment accelerates the amount and rate of corrosion.

[0004] In addition, with the gradual increase in the calorific value of garbage, it exceeds the rated value of the design of the garbage incineration plants built in the early days, and the garbage incineration boilers are also developing towards large-scale and high-parameterization. The large amount of ash powder generated during the combustion of garbage washes the heating surface tubes, causing the outer surface of the heating surface tubes to be worn to varying degrees. Under the combined effect of the above-mentioned factors, the heating surface tubes are continuously oxidized, corroded and worn from the outside to the inside, causing them to gradually become thinner. When they cannot withstand the water vapor pressure in the tubes, an explosion accident will occur, thus causing a safety hazard.

[0005] Therefore, in actual practice, metal materials are often built up on the surface of the heated surface, such as using stainless steel powder or Inconel 625 alloy powder for laser welding, to appropriately extend its service life, but the effect is limited. Since the temperature resistance of stainless steel has an upper temperature limit, it cannot be effectively protected above 800°C. Although Inconel 625 alloy has excellent corrosion resistance, it lacks in wear resistance and ultra-high temperature oxidation resistance. At the same time, the alloy powder used for laser surfacing on the market is mostly delivered by airflow, which has relatively high requirements on the sphericity and particle size of the powder. Summary of the invention

[0006] In order to solve the above-mentioned problems, the present application provides an alloy powder for laser surfacing welding and a preparation method thereof, which can fully cope with the challenges of complex corrosive environment and high-temperature erosion and wear in waste incinerators, so as to prolong the service life of the equipment and improve safety and stability.

[0007] In the first aspect, the present application provides an alloy powder suitable for laser cladding of a waste incinerator, which adopts the following technical solution: An alloy powder suitable for laser surfacing welding of a waste incinerator, wherein the alloy powder comprises the following components by mass percentage: C≤0.10%, Cr 20.0-23.0%, Mo 8.0-10.0%, Nb 3.15-4.15%, Fe≤0.50%, Sc≤0.005%, Al≤0.40%, Ti≤0.40%, Si≤1.0%, and the rest is Ni.

[0008] Furthermore, the alloy powder includes the following components in percentage by mass: C≤0.10%, Cr20.0-21.0%, Mo 9.0-10.0%, Nb 3.50-3.90%, Fe≤0.40%, Sc≤0.002%, Al≤0.40%, Ti≤0.40%, Si≤1.0%, and the rest is Ni.

[0009] Furthermore, the alloy powder includes the following components in percentage by mass: C≤0.10%, Cr21.0%, Mo 9.0%, Nb 3.60%, Fe≤0.40%, Sc 0.002%, Al≤0.40%, Ti≤0.40%, Si 0.80%, and the rest is Ni.

[0010] By adopting the above technical solution and using the alloy powder provided above for laser cladding, a cladding layer with excellent corrosion resistance and high temperature erosion and wear resistance can be formed on the surface of key components such as the heating tubes of the waste incinerator. This cladding layer can effectively resist the erosion of complex environments such as high temperature, high humidity, and corrosive gases generated during the waste incineration process, thereby significantly improving the service life and safety of the equipment.

[0011] In the second aspect, the present application provides a method for preparing alloy powder suitable for laser cladding of waste incinerators, which adopts the following technical solution: A method for preparing alloy powder suitable for laser surfacing welding of a waste incinerator comprises the following steps: mixing ingredients according to a formula, then sending the raw materials into a vacuum melting chamber and performing a vacuum treatment; melting the metal raw materials into metal liquid through electromagnetic induction and passing the metal liquid into an atomization chamber through a guide pipe for atomization granulation to obtain the alloy powder.

[0012] By adopting the above technical scheme, the alloy powder suitable for laser surfacing welding of waste incinerators obtained by this preparation method has the advantages of high purity, uniform particle size, regular shape, high laser surfacing efficiency and good quality. At the same time, the preparation method also has the characteristics of high production efficiency, low energy consumption, good environmental protection, etc., which helps to reduce production costs and reduce environmental pollution.

[0013] Furthermore, in the vacuum melting chamber, the temperature is raised in stages to 1430-1585°C.

[0014] Furthermore, the specific heating program is: in the 0-10min stage, slowly heat up to 40-450℃, then keep warm for 5min, then in 15-30min, slowly heat up to 1150-1200℃, and keep warm for 2min, then in 32-35min, quickly heat up to 1430-1585℃, and continue for 40-250min.

[0015] By adopting the above technical solution, with the help of the staged heating technical solution, the smelting process can be optimized, the quality of alloy powder can be improved, the production efficiency can be improved, and the adaptability can be enhanced.

[0016] Furthermore, during the atomization granulation process, the air flow velocity is controlled to be 15-20 Nm³ / min, and the gas pressure is controlled to be 0.7-1.3 MPa.

[0017] Furthermore, during the atomization granulation process, the spray angle, that is, the angle between the gas spray direction and the metal liquid flow direction, is 3-6°.

[0018] By adopting the above technical solution, precise control of air flow velocity, gas pressure and injection angle can improve the repeatability of the process, ensure that stable and high-quality alloy powder can be obtained in each atomization granulation process, and ensure the particle size and uniformity of the alloy powder as well as the regularity of its shape.

[0019] In summary, the present application has the following beneficial effects: 1. The present application refines the grains and reduces the defects at the grain boundaries by carefully designing the composition of the alloy powder, especially the introduction of the rare earth element Sc, so that the cladding layer formed by the alloy powder as welding powder after laser cladding has excellent wear resistance and corrosion resistance. The heat pipes laser cladding with these alloy powders can operate stably for a long time in the harsh working environment of the waste incinerator, reduce equipment failures and maintenance costs caused by corrosion and wear, and thus improve the operating efficiency and reliability of the entire waste incineration system; 2. The alloy powder suitable for laser surfacing welding of waste incinerators obtained through a precise preparation process in this application has the advantages of high purity, uniform particle size, regular shape, high laser surfacing efficiency and good quality. At the same time, the preparation method also has the characteristics of high production efficiency, low energy consumption, good environmental protection, etc., which helps to reduce production costs and reduce environmental pollution. DETAILED DESCRIPTION

[0020] The present application is further described in detail below in conjunction with the examples. Except for the special instructions below, the raw materials used in the present application are all common commercially available materials.

[0021] Performance testing A 12Cr1MoVG seamless alloy steel pipe (wall thickness 6.45 mm) was selected as the base material, and a mixed gas of argon and helium was used for airflow powder feeding. The powder was prepared by each embodiment and comparative example, and the powder feeding speed was 120-180 g / min. The laser used a solid laser source with a power of 3150 w to perform laser surfacing. The thickness of the surfacing layer was 2 mm. The sample obtained after laser surfacing was placed in a waste incinerator as a heating surface tube. The test cycle was 1 year. After one year, the sample was retrieved and its annual corrosion amount was tested, with the deepest point corrosion pit as the measurement target. A 12Cr1MoVG steel plate (thickness 20 mm) was selected as the base material, and a mixed gas of argon and helium was used for airflow powder feeding. The powder was prepared by each embodiment and comparative example, and the powder feeding speed was 120-180 g / min. The laser used a solid laser source with a power of 3150 w for laser surfacing. The sample obtained after laser surfacing was cut into 57 mm × 26 mm × 6 mm high-temperature erosion wear-resistant samples, and preheated for 20 min under 500 ° C dry heat conditions in a furnace, and then a performance test was carried out with reference to the ASTM G65-2016 dry sand wear test standard. The mass of the sample before and after the test was tested, and its loss rate was calculated.

[0022] Example 1 An alloy powder suitable for laser surfacing welding of a waste incinerator, wherein the alloy powder is composed of the following components by mass percentage: C 0.10%, Cr 20.0%, Mo 8.0%, Nb 3.15%, Fe 0.50%, Sc 0.005%, Al 0.40%, Ti 0.40%, Si 1.0%, and the balance is Ni; The above alloy powder is prepared by the following preparation method: The ingredients are mixed according to the formula, and then the raw materials are sent to the vacuum melting chamber. The vacuum treatment adopts a staged heating strategy, specifically: in the 0-10min stage, the temperature is slowly raised to 220℃, and then kept warm for 5min, then in 15-30min, the temperature is slowly raised to 1150℃, and kept warm for 2min, then in 32-35min, the temperature is quickly raised to 1515℃, and it lasts for 190min; through electromagnetic induction, the metal raw materials are melted into metal liquid and enter the atomization chamber through the guide tube for atomization granulation. During the atomization granulation process, the air flow velocity is controlled to 15Nm³ / min, the gas pressure is controlled to 0.9 MPa, and the injection angle, that is, the angle between the gas injection direction and the metal liquid flow direction, is controlled to 4°. The atomized alloy powder is collected and then passed through 20 mesh and 40 mesh sieves in turn to obtain spherical powder particles with a particle size of 95% within 20-38μm.

[0023] Example 2 An alloy powder suitable for laser surfacing welding of a waste incinerator, wherein the alloy powder is composed of the following components by mass percentage: C 0.10%, Cr 23.0%, Mo 8.0%, Nb 3.15%, Fe 0.50%, Sc 0.005%, Al 0.40%, Ti 0.40%, Si 1.0%, and the balance is Ni; The preparation method of the above alloy powder is the same as that of Example 1.

[0024] Example 3 An alloy powder suitable for laser surfacing welding of a waste incinerator, wherein the alloy powder is composed of the following components by mass percentage: C 0.10%, Cr 23.0%, Mo 10.0%, Nb 3.15%, Fe 0.50%, Sc 0.005%, Al 0.40%, Ti 0.40%, Si 1.0%, and the balance is Ni; The preparation method of the above alloy powder is the same as that of Example 1.

[0025] Example 4 An alloy powder suitable for laser surfacing welding of a waste incinerator, wherein the alloy powder is composed of the following components by mass percentage: C 0.10%, Cr 23.0%, Mo 10.0%, Nb 4.15%, Fe 0.50%, Sc 0.005%, Al 0.40%, Ti 0.40%, Si 1.0%, and the balance is Ni; The preparation method of the above alloy powder is the same as that of Example 1.

[0026] Example 5 An alloy powder suitable for laser surfacing welding of a waste incinerator, wherein the alloy powder is composed of the following components by mass percentage: C 0.10%, Cr 23.0%, Mo 10.0%, Nb 4.15%, Fe 0.40%, Sc 0.005%, Al 0.40%, Ti 0.40%, Si 1.0%, and the balance is Ni; The preparation method of the above alloy powder is the same as that of Example 1.

[0027] Example 6 An alloy powder suitable for laser surfacing welding of a waste incinerator, wherein the alloy powder is composed of the following components by mass percentage: C 0.10%, Cr 23.0%, Mo 10.0%, Nb 4.15%, Fe 0.40%, Sc 0.002%, Al 0.40%, Ti 0.40%, Si 1.0%, and the balance is Ni; The preparation method of the above alloy powder is the same as that of Example 1.

[0028] Example 7 An alloy powder suitable for laser surfacing welding of a waste incinerator, wherein the alloy powder is composed of the following components by mass percentage: C 0.10%, Cr 23.0%, Mo 10.0%, Nb 4.15%, Fe 0.40%, Sc 0.002%, Al 0.40%, Ti 0.40%, Si 0.80%, and the balance is Ni; The preparation method of the above alloy powder is the same as that of Example 1.

[0029] Example 8 An alloy powder suitable for laser surfacing welding of a waste incinerator, wherein the alloy powder is composed of the following components by mass percentage: C 0.10%, Cr 21.0%, Mo 10.0%, Nb 4.15%, Fe 0.40%, Sc 0.002%, Al 0.40%, Ti 0.40%, Si 0.80%, and the balance is Ni; The preparation method of the above alloy powder is the same as that of Example 1.

[0030] Example 9 An alloy powder suitable for laser surfacing welding of a waste incinerator, wherein the alloy powder is composed of the following components by mass percentage: C 0.10%, Cr 21.0%, Mo 9.0%, Nb 4.15%, Fe 0.40%, Sc 0.002%, Al 0.40%, Ti 0.40%, Si 0.80%, and the balance is Ni; The preparation method of the above alloy powder is the same as that of Example 1.

[0031] Example 10 An alloy powder suitable for laser surfacing welding of a waste incinerator, wherein the alloy powder is composed of the following components by mass percentage: C 0.10%, Cr 21.0%, Mo 9.0%, Nb 3.50%, Fe 0.40%, Sc 0.002%, Al 0.40%, Ti 0.40%, Si 0.80%, and the balance is Ni; The preparation method of the above alloy powder is the same as that of Example 1.

[0032] Embodiment 11 An alloy powder suitable for laser surfacing welding of a waste incinerator, wherein the alloy powder is composed of the following components by mass percentage: C 0.10%, Cr 21.0%, Mo 9.0%, Nb 3.90%, Fe 0.40%, Sc 0.002%, Al 0.40%, Ti 0.40%, Si 0.80%, and the balance is Ni; The preparation method of the above alloy powder is the same as that of Example 1.

[0033] Example 12 An alloy powder suitable for laser surfacing welding of a waste incinerator, wherein the alloy powder is composed of the following components by mass percentage: C 0.10%, Cr 21.0%, Mo 9.0%, Nb 3.60%, Fe 0.40%, Sc 0.002%, Al 0.40%, Ti 0.40%, Si 0.80%, and the balance is Ni; The preparation method of the above alloy powder is the same as that of Example 1.

[0034] Comparative Example 1 An alloy powder suitable for laser surfacing welding of a waste incinerator, wherein the alloy powder is composed of the following components by mass percentage: C 0.10%, Cr 21.0%, Mo 9.0%, Nb 3.60%, Fe 0.40%, Mn 0.30%, Al 0.40%, Ti 0.40%, Si 0.80%, and the balance is Ni; The preparation method of the above alloy powder is the same as that of Example 1.

[0035] The alloy powders prepared in the above-mentioned Examples 1-12 and Comparative Example 1 were subjected to performance testing tests according to the aforementioned testing methods.

[0036]

[0037] It can be seen from the above table that the alloy powders prepared by Examples 1-12 of the present application, when used as welding powders for laser cladding of waste incinerators, show excellent performance. The cladding layers formed by these alloy powders on the surface of the heated tubes not only have excellent corrosion resistance, but can also maintain their structural integrity and performance stability in complex corrosive environments such as waste incinerators with high temperature, high humidity, and corrosive gases, and also have significant high-temperature wear resistance. After a one-year furnace operation hanging sample test, the annual corrosion amount of the sample is maintained at 0.02-0.09mm. At the same time, in the external wear performance test, the sample loss rate before and after is maintained at 0.021-0.026%. Among all the above embodiments, the various performances of Example 12 are the best, so it can be used as a preferred example in the present application; In Comparative Example 1, the alloy powder composition is mainly the common Inconel 625 alloy composition on the market. Compared with Example 12, the only difference is that the alloy composition contains 0.30% Mn and does not contain 0.002% Sc. From the data performance, the cladding layer formed by laser surfacing welding on the surface of the heated tube by the alloy powder prepared in Comparative Example 1 has an annual corrosion amount of 0.32 mm after a one-year furnace operation hanging sample test. At the same time, in the external wear performance test of the sample, the loss rate of the sample before and after is maintained at 0.095%. All performances are inferior to those of Example 12; The reasons may be as follows: the introduction of rare earth element Sc effectively improves the wear resistance and corrosion resistance of the alloy powder as welding powder. Sc is an effective grain boundary strengthening element, which can significantly improve the corrosion resistance and high temperature resistance of the alloy. A trace amount of Sc may help to form a denser and more stable oxide protective film, thereby improving the corrosion resistance of the alloy. At the same time, Sc may also improve the high temperature wear resistance of the alloy by refining the grains and reducing the defects at the grain boundaries. At the same time, since Mn is an excellent deoxidizing and desulfurizing agent, generally in a composite corrosion environment at high temperature, that is, sulfur and oxygen exist at the same time, the deoxidizing and desulfurizing effects of Mn work together to improve the corrosion resistance of the alloy. In addition, Mn can also increase the strength and hardness of the alloy, improve the hardenability of the steel, and make the steel obtain higher hardness and strength after quenching. However, we found here that when the alloy powder of the embodiment of the present application does not contain Mn, this anti-corrosion effect on the sulfur-oxygen composite corrosion environment does not disappear. This may be an additional effect brought about by the introduction of Sc. Sc may undergo specific chemical reactions with sulfur and oxygen to form stable compounds or protective films, thereby preventing sulfur and oxygen from further corroding the alloy matrix. It may also change the microstructure of the alloy powder, resulting in changes in the composition and distribution of the original phase. These changes in microstructure may help to improve the corrosion resistance of the alloy, and only a very small amount of Sc is required to achieve it.

[0038] In summary, the heated tubes laser-welded with these alloy powders can operate stably for a long time in the harsh working environment of the waste incinerator, reduce equipment failures and maintenance costs caused by corrosion and wear, and thus improve the operating efficiency and reliability of the entire waste incineration system.

[0039] The above are all modifications without creative contribution or solutions that obviously constitute technical inspiration that can be made to the present embodiment as needed by technical personnel in this field after reading this specification, but they should be protected by patent law as long as they are within the scope of the claims of this application.

Claims

1. An alloy powder suitable for laser surfacing welding of waste incinerators, characterized in that: The alloy powder comprises the following components in percentage by mass: C≤0.10%, Cr 20.0-23.0%, Mo 8.0-10.0%, Nb 3.15-4.15%, Fe≤0.50%, Sc≤0.005%, Al≤0.40%, Ti≤0.40%, Si≤1.0%, and the rest is Ni.

2. The alloy powder suitable for laser surfacing welding of a waste incinerator according to claim 1 is characterized in that: The alloy powder comprises the following components in percentage by mass: C≤0.10%, Cr 20.0-21.0%, Mo 9.0-10.0%, Nb 3.50-3.90%, Fe≤0.40%, Sc≤0.002%, Al≤0.40%, Ti≤0.40%, Si≤1.0%, and the rest is Ni.

3. The alloy powder suitable for laser surfacing welding of a waste incinerator according to claim 1 is characterized in that: The alloy powder comprises the following components in terms of mass percentage: C≤0.10%, Cr 21.0%, Mo 9.0%, Nb 3.60%, Fe≤0.40%, Sc 0.002%, Al≤0.40%, Ti≤0.40%, Si 0.80%, and the remainder is Ni.

4. The method for preparing alloy powder suitable for laser surfacing welding of waste incinerators according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: mixing ingredients according to the formula, and then sending the raw materials into a vacuum melting chamber and performing vacuum treatment; melting the metal raw materials into metal liquid through electromagnetic induction and passing the metal liquid into an atomizing chamber through a guide pipe for atomization granulation to obtain the obtained product.

5. The method for preparing alloy powder suitable for laser surfacing welding of waste incinerator according to claim 4, characterized in that: In the vacuum melting chamber, the temperature is raised in stages to 1430-1585°C.

6. The method for preparing alloy powder suitable for laser surfacing welding of waste incinerator according to claim 5, characterized in that: The specific heating procedure is: in the 0-10min stage, slowly heat up to 40-450℃, then keep warm for 5min, then in 15-30min, slowly heat up to 1150-1200℃, and keep warm for 2min, then in 32-35min, quickly heat up to 1430-1585℃, and continue for 40-250min.

7. The method for preparing alloy powder suitable for laser surfacing welding of waste incinerator according to claim 4, characterized in that: During the atomization granulation process, the air flow rate is controlled at 15-20 Nm³ / min and the gas pressure is controlled at 0.7-1.3 MPa.

8. The method for preparing alloy powder suitable for laser surfacing welding of waste incinerator according to claim 4, characterized in that: During the atomization granulation process, the injection angle, that is, the angle between the gas injection direction and the metal liquid flow direction, is 3-6°.

Citation Information

Patent Citations

  • Special copper alloy powder for laser-sensing composite fusion-covering high-strength high-conductivity copper alloy coating

    CN103074517A

  • 12CrNi2Re alloy steel powder used for laser material additive manufacturing and preparation method and application thereof

    CN107747038A

  • Plasma surfacing alloy powder and preparation method and application thereof

    CN109182954A

  • Nickel-based alloy for corrosion prevention of garbage incinerator, preparation method of nickel-based alloy powder and composite material

    CN113737058A

  • Nickel-based alloy powder for protecting waste incineration boiler and preparation method of coating

    CN116159993A